Evaluating Bicycle and Pedestrian Infrastructure in Environmental Justice Communities. (June 2018) - Rahman, Ziaur; Nostikasari, Dian; Donavalli, Bharath; Madanu, Sunil; Roeglin, Nicole; Mattingly, Stephen; Casey, Colleen
Abstract : Background: The recognition of the relationships between transportation, land use, infrastructure and services with health outcomes has prompted response from federal, state, regional, and local governments to integrate health objectives into their planning and policymaking process. The study applies an index-based analytical tool that can help transportation agencies in the decision making process related to active transportation investments. This paper has the following objectives: Present sketch planning metrics to assess safety and physical activity of pedestrian and bicyclists at both segments and intersections. Perform a comparative spatial analysis of transportation facilities that serve environmental justice (EJ) populations and as a control, transportation facilities that serve non-EJ populations Methods: Using an Environmental Justice Index (EJI) as a tool for mapping concentrations of low-income and minority group populations (effectively called an EJ population) in a given region, the researchers select fifteen Census Block Groups (CBGs) in the City of Arlington, Texas, for spatial analysis. The fifteen CBG locations include both EJ (12) and non-EJ (3) populations. The project-level analysis collects data through a visual assessment of street segments and intersections with an observational survey by a trained observer. The survey captures broad criteria that potentially affect the safety risk to either pedestrians or bicyclists and overall walkability and bikeability of road segments and intersections. Results: The average safety index (0-1 scale) for both pedestrians (0.23) and bicyclists (0.25) in the non-EJ category segments appear lower than EJ category segments, 0.37 and 0.31 respectively. The bikeability and walkability indices on segments also reflect a similar trend as safety. The physical activity index levels reflect more suitable conditions at non-EJ intersections. Irrespective of CBG type, segments on arterial roads show higher safety for pedestrians compared to minor arterials and collectors; however, bicyclist safety does not improve for arterials. Overall, the Arlington infrastructure does not have a positive impact on safety or physical activity; however, the EJ CBGs' infrastructure provides a minimally positive impact on safety. Conclusions: The developed indices provide an analytical framework to assess the safety and physical activity environment of transportation infrastructure. These indices allow transportation agencies to evaluate two or more corridors, regions and networks and may help inform the investment decision making process, strategic planning, policy or programming analysis and resource planning. While EJ populations may have access to slightly better facilities than non-EJ populations in Arlington, Texas, none of the facilities should be deemed adequate for bicyclists and pedestrians.